Biomaterials for Regenerative Medicine Approaches for the Anterior Segment of the Eye. Issue 10 (1st February 2018) - Williams, Rachel; Lace, Rebecca; Kennedy, Stephnie; Doherty, Kyle; Levis, Hannah
Abstract: The role of biomaterials in tissue engineering and regenerative medicine strategies to treat vision loss associated with damage to tissues in the anterior segment of the eye has been studied for several years. This has mostly involved replacement and support for the cornea and conjunctiva. These are complex tissues with specific functional requirements for different parts of the tissue. Amniotic membrane (AM) is used in clinical practice to transplant autologous or allogenic cells to the corneal surface. Fibrin gels have also progressed to clinical use under specific conditions. Alternatives to AM such as collagen gels, other natural materials, for example keratin and silks, and synthetic polymers have received considerable attention in laboratory and animal studies. This experience is building a body of evidence to demonstrate the potential of tissue engineering and regenerative medicine in corneal and conjunctival reconstruction and can also lead to other applications in the anterior segment of the eye, for example, the trabecular meshwork. There is a real clinical need for new procedures to overcome vision loss but there are also opportunities for developments in ocular applications to lead to biomaterials innovations for use in other clinical areas. Abstract : Biomaterials have an important role in the development of tissue engineering and regenerative medicine strategies to replace or support reconstruction of the ocular surface to overcome vision loss. Current clinical practice uses amniotic membrane to transplant cells to the cornea but natural and synthetic polymers are under development with the potential to provide increased availability and control of the properties.